The Role of Neutrophil Gelatinase-Associated Lipocalin (NGAL) as a Biomarker in Predicting the Function of Kidney Grafts: A Literature Review - Alexander A. Dermanis; Dominic Thompson; Georgios Koimtzis (Journal of Clinical Medicine, 2026)
Background/Objectives: Kidney transplantation is the gold standard treatment for end-stage renal failure. Numerous studies have sought to identify biomarkers that can predict early outcomes. Neutrophil gelatinase-associated lipocalin (NGAL) is a biomarker that is hypothesised to be an important predictor of early surgical outcomes. Methods: A targeted narrative search was performed using prespecified search terms. Reference lists were searched to identify and yield more articles. Discussion: This review has identified several domains in which urinary and serum NGAL may be useful as well as limitations in its application. Conclusions: NGAL is a promising biomarker; however, further research is necessary to establish best practice in its use in the early post-operative phase.